Relationship between personal empowerment and self-identity development among adolescents in Malaysia - A`Dawiyah Ismail,; Zaizul Ab Rahman,; Siti Norul Huda Sheikh Abdullah,; Muhammad Nuruddin Sudin,; Azianura Hani Shaari,; Norulhuda Sarnon @ Kusenin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Adolescents are susceptible to negative influences and activities via social media, surroundings and peers. Cyberbullying, dangerous online games, accessible pornographic content are some examples of negativities which adolescents tend to be drawn into, either knowing or unknowingly, without giving much thought to the consequences of their actions/engagements. To address this, a self-empowerment program has been developed and tailored for school teens. This program covers faith, positivity, social relationship, role-modeling and self-reflection. A total of 219 teenagers aged between 12 to 17 years old participated in this study. 61 out of the 219 teens formed the control group. Adolescents under the control group did not participate in the self-empowerment program whilst the rest of the 158 teens underwent the program. A survey was carried out to both the control and non-control groups of teenagers to measure the acceptance and the projected impact on the teens who participated in the program. Overall, positive responses were recorded with an average score of 5.10/6.00 for the non-control groups and 4.81/6.00 for the control group.